The invisible landscape : Revealing our place in the world. - Liss, David (Ottawa : National Gallery of Canada Ottawa, 2005)
Broker, Bertram ; Carr, Emily ; Ewen, Paterson ; Flack, Robert ; Goodwin, Betty ; Harris, Lawren S. ; King, Holly ; Lawson, Ernest ; Macdonald, Jock ; Poitras, Jane Ash ; Poulin, Roland ; Renner, Eric ; Richter, Gerhard ; Shadbolt, Jack ; Sivuraq, Thomas ; Viola, Bill ; Witkin, Joel-Peter
Engels
Exhibition. The invisible landscape : Revealing our place in the world. Medicine Hat Museum and Gallery Medicine Hat, 17.12.2005 - 26.03.2006.
boek